(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
The present study was conducted to investigate the effects of probiotic on growth performance, gut health, viability, carcass yield traits and cost benefit analyses etc., of broiler chicken from d1-28 days. A total of 192 day-old broiler chicks (Ross 308) was assigned into four dietary treatment groups, i.e. D1 (Control), D2 (Poultry Starsol), D3 (Avilac plus) and D4 (Avibac), and each treatment replicated six times with eight birds per replicate in a completely randomized design. The chicks were raised in battery cages all the trial period. Ready-made starter diet (crumble) was fed the chicks up to 14 days, after that, grower (pellet) diet fed the broiler from d15 to 28 days. The water treated with probiotics at the rate of 1.0 g L-1 (Poultry Starsol), 1.0 ml L-1 (Avilac plus) and 1.0 g L-1 (Avibac) in D2, D3 and D4 treatment groups, respectively, and supplied the birds ad libitum entire the trial period. Data on feed intake (FI), body weight gain (BWG), feed conversion ratio (FCR) and livability (%) were collected. Apart from this, caecal digesta sample was taken on 28 days to determine the gut microflora population, i.e. total viable count (TVC) and total lactobacilli count (TLC) of broilers. Carcass characteristics (dressing %, blood weight, drumstick weight, thigh weight, breast weight %) and cost benefit were also calculated on the last day of trial period to assess the different meat cuts and the profitability of broiler. The data revealed that FI, viability (%), TVC and TLC of broilers had no difference (P>0.05) between treatment on 28d. Except for first week, BWG was improved significantly (P<0.05) in the birds fed probiotics during d1-21 and d1-28, respectively. Superior FCR values (1.30, 1.34) were observed in the broilers of probiotics supplemented groups from d1-28 days of age. The results of carcass traits were influenced significantly (P<0.05) by dietary treatment. The percentage of breast weight, thigh weight, dressing yield, drumstick weight and blood weight was increased (P<0.05) in the supplemental group compared to control. Higher (P<0.01) net profit was observed in the birds of probiotics supplemented group than that of control group. It can be concluded that broiler responded positively as a result of probiotics supplementation in water, and can be raised profitably under farming condition with low cost. Int. J. Agril. Res. Innov. Tech. 10(1): 28-34, June 2020